2017
DOI: 10.1002/smll.201701201
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Action Cancer Therapy with Targeted Porous Silicon Nanovectors

Abstract: There is a pressing need to develop more effective therapeutics to fight cancer. An idyllic chemotherapeutic is expected to overcome drug resistance of tumors and minimize harmful side effects to healthy tissues. Antibody-functionalized porous silicon nanoparticles loaded with a combination of chemotherapy drug and gold nanoclusters (AuNCs) are developed. These nanocarriers are observed to selectively deliver both payloads, the chemotherapy drug and AuNCs, to human B cells. The accumulation of AuNCs to target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…D) Viability of human B lymphocytes when exposed to pSiNPs with different cargoes with or without anti‐CD20 functionalization and with or without the application of an electromagnetic field in the microwave (μW) region. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Psi For Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…D) Viability of human B lymphocytes when exposed to pSiNPs with different cargoes with or without anti‐CD20 functionalization and with or without the application of an electromagnetic field in the microwave (μW) region. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Psi For Drug Deliverymentioning
confidence: 99%
“…To help overcome tumor resistance to chemotherapeutics, Cifuentes‐Rius et al. explored the synergistic effect of combining hyperthermia and the anticancer drug, camptothecin, in B‐lymphocytes (Figure C) . As cancer cells are more vulnerable to higher temperatures compared to normal cells, hyperthermia stimulates the uptake of chemotherapy drugs in tumor cells .…”
Section: Psi For Drug Deliverymentioning
confidence: 99%
“…Despite increasing the circulation time of the drug and its accumulation in tumors, the loading capacity and controlled release of most nanotherapeutics is still a bottleneck in the field. Biodegradable [19][20][21], non-toxic [22][23][24], non-immunogenic [22,23,25] porous silicon nanoparticles (pSiNP), offer a platform for the vectorization of hydrophobic drugs in high quantities into the pores while allowing the immobilization of targeting antibodies on the nanoparticle's surface [26,27]. As CPT is highly hydrophobic, an encapsulation effect based on non-covalent bonds is generated within the water-repellent pores of the pSiNP.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that hyperthermia-inducing nanoclusters delivered via targeted pSiNPs were an effective chemosensitizer. 27 Although the co-delivery of chemotherapeutic and siRNA has been reported using mesoporous silica nanoparticles, 16,28,29 to date, the use of porous silicona highly biodegradable biomaterial as opposed to silica 30 for the co-delivery of siRNA and chemotherapy drug has not been reported. Thus, the use of siRNA technology in combination with pSiNPs to inhibit MRP1 presents itself to be a logical target in reversing the chemotherapy resistance in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…17 We have shown that pSiNPs are suitable for conjugation with moieties to recognize and target a specific cell population, which is of paramount importance to enhance therapy efficacy and reduce side effects. 26,27 Among all targeting moieties, single-domain antibodiesderived from naturally occurring heavy-chain-only antibodies 31 and also known as nanobodieshave been recently shown to present various advantageous properties over their conventional antibody counterparts such as their small size (∼15 kDa compared to ∼150 kDa for antibodies), high stability and a strong antigen-binding affinity. 32 Here, we chose to utilize two different receptor targets for our nanobodiesthe epidermal growth factor receptor (EGFR) and prostate specific membrane antigen (PSMA).…”
Section: Introductionmentioning
confidence: 99%